(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Intruduction: Pregnancy in grand multipara has been considered as high risk because there are higher chance of complication during pregnancy, labour and puerperium. Objective: To evaluate various maternal and fetal complication associated with a grand multipara during pregnancy, delivery and puerperium. Methods: This prospective study was carried out from 1st January 2008 to 31st December 2008 in Obstetrics & Gynecology Department of Sylhet MAG Osmani Medical College & Hospital, Sylhet. 300 grand multipara pregnant patients were selected those who got admitted in Department of Obstetrics & Gynecology, SOMCH during that period. Result: It was found that incidence of grand multipara was 6.60%. Majority of the patient were between 3135 years old (43%). 66% patients never had anternal checkup, Caesarean section was high about 47%. Complications during labour were also high. It was about 51.67%. Maternal morbidity was about 16%. Perinatal mortality was about 11%. Conclusion: This study showed that grand multipara is a major risk for obstetrical outcome and needs strick supervision and good antenatal, intranatal and postnatal care. J Bangladesh Coll Phys Surg 2016; 34(4): 184-187